The Effectivity of Problem Based Learning with Scaffolding on Creative Thinking Ability of Senior High School Students in Terms of Gender - Herman Jufri Andi; Chairatul Umamah; Wayan Suana (STKIP Singkawang, 2021)
This study aims to explain how the effectiveness of problem based learning with scaffolding on creative thinking abilities of senior high school students in terms of gender on the subject of Static Fluid. This type of research is quasi experimental using nonequivalent control group design. There are two classes in this study, namely the control class just with problem based learning and experimental class using problem based learning with scaffolding. The test instrument used was essay question. Conclusions are drawn based on results of data processing and analysis using T-test and two-way anova with SPSS 24.0. Based on the results of analysis and discussion, in this study the following conclusions were obtained: (1) Students creative thinking ability a taught using problem based learning with scaffolding were better than students' creative thinking ability taught using only problem based learning; (2) There are not differences in students' creative thinking abilities in terms of gender; (3) There is no an interaction between problem based learning with scaffolding with gender on students' creative thinking abilities. (4) Using problem based learning with scaffolding of students' creative thinking abilities in physics is more effective with an effect size value of 0.645 with a medium category.